Isolation and characterization of epithelial cells and fibroblasts from the human penile urethra - Brownell, David; Elia, Elissa; Pellerin, Félix-Antoine; Chabaud, Stéphane; Larochelle, Sébastien; Moulin, Véronique J.; Laungani, Alexis; Bolduc, Stéphane (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionUrethral strictures and hypospadias are common urological conditions for which autologous reconstruction remains challenging. Tissue engineering offers a promising alternative, yet current strategies often rely on heterotopic cell sources, potentially limiting functional integration. Here, we report the first isolation and characterization of epithelial and stromal cells from distinct regions of the human penile urethra: the spongy urethra and the proximal and distal fossa navicularis.MethodsCells were isolated from the three regions of the penile urethra in 12 donors. Detailed characterization was performed for 3–4 donors, assessing yield, growth parameters, immunophenotype, and progenitor preservation. We evaluated 3-, 4-, and 6-mm biopsies to determine the minimal tissue size required for clinically relevant cell yields. Multiple enzymatic protocols were compared, using thermolysin or dispase II for epithelial-stromal separation, followed by collagenase ± elastase digestion for stromal cell recovery.ResultsCell extraction had a 100% success rate across all tested protocols. The combination of dispase and a 4-h collagenase/elastase digestion yielded the highest cell numbers and clonogenic potential. All biopsy sizes produced sufficient cells for tissue engineering.DiscussionThese findings demonstrate the feasibility of harvesting high-quality, organ-specific autologous cells from minimal urethral biopsies. In addition to their clinical potential, these cells provide a foundation for preclinical disease modelling using patient-derived pathological cells, which are currently unavailable for in vitro studies of urethral disorders.